Maternal Mortality in Chiapas: An Unfinished Story - Héctor Javier Sánchez Pérez; Marcos Arana Cedeño (Social Medicine Publication Group, 2015)
As part of Mexico's strategy to achieve Millennium Development Goal 5.A (reduction of maternal mortality by ¾), efforts have been made to increase the number of births occurring in institutional settings. These efforts were intended to improve a key indicator for Goal 5: the number of deliveries "attended by skilled health personnel." The practical consequence of these efforts has been that hospitals are seeing ever-increasing numbers of normal deliveries. As an unintended consequence, the quality of care provided to true obstetrical emergencies has decreased. This problem is particularly severe in those regions of Mexico, like Chiapas state, that are characterized by high levels of poverty and social marginalization. Maternal mortality rates in these areas are high. Importantly, most of these maternal deaths occur in the hospital. With the goal of promoting deliveries attended by "skilled personnel", obstetrical services at the primary level have been dismantled, and there has been a tacit prohibition of deliveries by traditional midwives. The result has been that the reference hospitals have been overwhelmed with low-risk pregnancies and cannot adequately manage the volume of deliveries. This paper was originally published in Spanish as: Sánchez J, Arana Cedeño M. La muerte materna en Chiapas: una historia inacabada. In: Espinoza E, González Guzman R, Barría S, Sengupta A, editors. La lucha por el derecho a la salud in América Latina. San Salvador: Asociación Latinoamericana de Medicina Social y el Movimiento por la Salud de los Pueblos; 2014. p. 132-6. This translation and its publication were graciously approved by the Peoples Health Movement and the authors.